Relevance of Person-Organisation Fit in Predicting Organizational Commitment and Issues in Establishing Fit Through Employment Interviews - Natarajan, N. K.; Nagar, Dinesh (Prabandhan: Indian Journal of Management, 2010)
In the present day organizational context, one of the main challenges of HR managers is retention of talent. In the job-starved labour market, it may not be difficult to attract manpower but what most HR managers face is the dilemma of manpower iteration. The question that begs for an answer is 'why do people leave organizations?' A synthesis of this may reveal several reasons for this trend, but the major challenge is to predict this behaviour at the time of personnel selection and help organizations save time and resource in induction and training of personnel who eventually leave in search of better pastures. It is imperative for any learning organization to understand the various dimensions effecting organizational commitment and predict the same for their potential employees based on Person-Organization fit.